2020
DOI: 10.1016/j.psj.2019.12.060
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effects of functional chalaza hydrolysates prepared from protease-A digestion on cognitive dysfunction and brain oxidative damages

Abstract: Our patented protease A–digested crude chalaza hydrolysates ( CCH ) show antioxidant abilities in vitro. The prophylactic effects of CCH on cognitive dysfunction and brain oxidative damages were investigated via a D-galactose ( DG )–injected mouse model in this study. Fifty-four mice were randomly divided into the following: (1) CON, 0.1 mL 0.9% saline (subcutaneous injection [ SC ] on the back)+distilled water (oral gavage); (2) DG, 100 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…+ 75 mg/kg silymarin in 1.5 mL pure water (oral gavage). The effective dosages of CCH for rats were based on our previous study (50 mg CCH-As/Kg BW, mouse; Chan et al., 2020 ) and calculated by dose translation between mice and rats ( Reagan-Shaw et al., 2008 ). TAA was injected three times per week (Monday, Wednesday, and Friday).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…+ 75 mg/kg silymarin in 1.5 mL pure water (oral gavage). The effective dosages of CCH for rats were based on our previous study (50 mg CCH-As/Kg BW, mouse; Chan et al., 2020 ) and calculated by dose translation between mice and rats ( Reagan-Shaw et al., 2008 ). TAA was injected three times per week (Monday, Wednesday, and Friday).…”
Section: Methodsmentioning
confidence: 99%
“…Our recently published work indicated that the contents of imidazole-ring dipeptide and free amino acids, for example, anserine, branched-chain amino acids, and aromatic amino acids (tyrosine and histidine) in protease A-digested crude chalaza hydrolysates ( CCH-As ) are increased hundred times than those in crude chalazae ( Yang et al., 2019 ; Chan et al., 2020 ). Thus, CCH-As showed hepatoprotective effects against chronic alcohol consumption and ameliorative effects against oxidative-stress induced cognitive dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…These pathogeneses cause a high expression of the following three syndromes: (1) oxidative stress, (2) inflammation, and (3) nervous dysfunction. Most of the collagen-based literature targets the antioxidative stress through different therapeutic ways [ 150 , 151 ]. Oxidative stresses cause cell death due to the mitochondrial dysfunction, apoptosis, and neuronal damage.…”
Section: Diseasementioning
confidence: 99%
“…Koizumi et al reveals the alteration in brain structure against dementia with the collagen hydrolysate intake [ 22 ]. Chan et al concludes with a significant decrease in memory loss, shrinkages in the dentate gyrus area, and neurodegeneration with the patent collagen hydrolysate [ 151 ]. The collagen hydrolysate with antioxidant amino peptides and anserine also results in the downregulation of amyloid β peptides [ 151 ].…”
Section: Diseasementioning
confidence: 99%
See 1 more Smart Citation